THEORETICAL INTERPRETATIONS OF THE CONCEPT OF POETIC MOTIVE - Khakimjonova Ra’no Olimjon qizi (Scholar Express Journals, 2021)
This article focuses on the literary assimilation and theoretical interpretations of the term motif, the relationship between motive and image as well as the tropical types of motifs, which differ from symbol, metaphor and similar features
Keywords: Poetic motif; lyrical motif; epic motif; symbol